A study of the tyre/road interface under wet conditions - Mosley, J. H. (Cranfield University, 1985)
This work addresses the problem of tyre tread pattern design for optimum wet grip performance. A mathematical model of tyre behaviour on wet roads has been developed. This utilizes the finite element method in the representation of tread pattern geometry. The performance of a particular tread pattern is found in terms of the fluid pressures and film thicknesses existing within the contact patch, under wet conditions. Many modern tread patterns are based on 'blocks', and a computer model has been developed specifically to assist the tyre designer in the design of these blocks for improved wet grip. Numerical results are presented both for complete contact patches and for individual tread blocks. To allow the use of the computer models by the tyre designer, with no specialist knowledge of the finite element method, special purpose mesh generation and plotting programs have been developed. Experiments have been undertaken whereby the fluid pressures and film thicknesses existing in the tyre contact patch have been measured under high speed conditions in the wet. These measure- ments were made on an indoor testing machine, and the techniques developed can be used in the routine evaluation of tyre wet grip performance. Some results of experiments performed on plain and simple patterned tyres are presented. The main purpose of this work was the development of the mathematical models which can be used for future research into, and design of, tyres for improved wet grip. However, some conclusions are made as to possible features which could be utilized in future tyre designs.